2008
DOI: 10.1111/j.1944-9720.2008.tb03292.x
|View full text |Cite
|
Sign up to set email alerts
|

The Linguistic Similarities of Spanish Heritage and Second Language Learners

Abstract: This article addresses the situation of lower‐proficiency heritage language learners of Spanish in terms of their linguistic similarities to second language learners. The analysis highlights grammatical and lexical features in the oral discourse of Spanish heritage and second language learners at intermediate and advanced levels of study, establishing common linguistic ground between the two groups. Given the similarities, the article emphasizes the current need for courses designed to accommodate lower‐profic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 41 publications
0
38
0
1
Order By: Relevance
“…Advanced HL students already have receptive and productive skills, and they usually have little need to develop their basic communicative abilities. They are closer to the native speaker norm than are lower‐proficiency speakers, who more closely resemble the L2 norm (see Lynch, 2008, for detailed discussion). Furthermore, a current “bio‐developmental definition” of native speaker (Davies, 1996, p. 156) also applies to HL speakers, as “an individual is a native speaker of the L1 learnt in childhood” (Cook, 1999, p. 186).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Advanced HL students already have receptive and productive skills, and they usually have little need to develop their basic communicative abilities. They are closer to the native speaker norm than are lower‐proficiency speakers, who more closely resemble the L2 norm (see Lynch, 2008, for detailed discussion). Furthermore, a current “bio‐developmental definition” of native speaker (Davies, 1996, p. 156) also applies to HL speakers, as “an individual is a native speaker of the L1 learnt in childhood” (Cook, 1999, p. 186).…”
Section: Discussionmentioning
confidence: 90%
“…Their first and only HL class disappointed them because the emphasis was on prescriptive grammar rather than oral proficiency. Lynch's (2008) study of five lower‐proficiency HL students and four L2 learners found that, even though all of the HL students had initially acquired and used Spanish as a first language (L1), their grammatical and lexical abilities in an oral interview strikingly resembled those of the L2 learners. Lynch attributed this linguistic similarity to the social exposure to the language: The HL learners spoke primarily English at home, used English as the main language of formal cognitive development and peer socialization, and did not have significant Spanish language contact experiences.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In sociolinguistic terms, immigrant parents are the first generation, their children second and their grandchildren are the third generation (Silva-Corvalán, 1994). Previous research has shown that each new generation of an immigrant community becomes less proficient in their HL (Lynch, 2008). When immigrant communities progressively replace their HL with the language of the socially or economically dominant group, ML, language shift takes place.…”
Section: Language Contact Language Anxiety and Immigrant Contextmentioning
confidence: 99%
“…(Montrul, 2005;2012), but it also has very important pedagogical implications. Researchers and practitioners alike debate over whether it is more advantageous to enroll adult L2 and HL students attending post-secondary education in the same classes or in different classes that meet their specific needs (Bowles, 2011a;Lynch, 2008;Mikulski, 2010;Potowski et al, 2009). HL and L2 learners' linguistic systems have been found to differ in terms of age of acquisition, learning context, language variety, or connections to language and culture.…”
Section: Introductionmentioning
confidence: 99%